Studi Fenomenologi: Gambaran Persepsi Lansia Awal Tentang Aktifitas Fisik Selama Satu Tahun Terakhir - linda pramusinta; Kristianto Dwi Nugroho (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Introduction: Physical activity is an activity that utilizes the body's limbs which refers to a healthy lifestyle, someone who diligently exercises every day will have physical fitness. In our bodies when doing physical activity will result in burning energy that is released through sweat, good and useful physical activity is one that is fun and flexible so that this physical activity is very good for the elderly to do. Method: The research used in this study is a qualitative study with a phenomenological research approach. This study aims to examine and explain precocious older adults' perceptions of physical activity over the past year in order to gain understanding, meaning, and phenomena. Participants who have obtained as many as 8 participants. The analysis used by using colaizzi data analysis. Results: This research produced four themes Themes found are causes of impact of pandemic, physical activity, social activity and hope . The hope of all participants is to be able to exercise for 30 minutes every day.